Chemoradiotherapy with or without panitumumab in patients with unresected, locally advanced squamous-cell carcinoma of the head and neck (CONCERT-1): a randomised, controlled, open-label phase 2 trial. Issue 2 (February 2015) - Mesía, Ricard; Henke, Michael; Fortin, Andre; Minn, Heikki; Yunes Ancona, Alejandro Cesar; Cmelak, Anthony; Markowitz, Avi B; Hotte, Sebastien J; Singh, Simron; Chan, Anthony T C; Merlano, Marco C; Skladowski, Krzysztof; et al.
Summary: Background: Panitumumab is a fully human monoclonal antibody that targets EGFR. We aimed to compare chemoradiotherapy plus panitumumab with chemoradiotherapy alone in patients with unresected, locally advanced squamous-cell carcinoma of the head and neck. Methods: In this international, open-label, randomised, controlled, phase 2 trial, we recruited patients with locally advanced squamous-cell carcinoma of the head and neck from 41 sites in nine countries worldwide. Patients aged 18 years and older with stage III, IVa, or IVb, previously untreated, measurable (≥10 mm for at least one dimension), locally advanced squamous-cell carcinoma of the head and neck (non-nasopharygeal) and an Eastern Cooperative Oncology Group performance status of 0–1 were randomly assigned (2:3) by an independent vendor to open-label chemoradiotherapy (three cycles of cisplatin 100 mg/m 2 ) or panitumumab plus chemoradiotherapy (three cycles of intravenous panitumumab 9·0 mg/kg every 3 weeks plus cisplatin 75 mg/m 2 ) using stratified randomisation with a block size of five. All patients received 70 Gy to gross tumour and 50 Gy to areas at risk for subclinical disease with standard fractionation. The primary endpoint was local-regional control at 2 years, analysed in all randomised patients who received at least one dose of their assigned protocol-specific treatment (chemotherapy, radiation, or panitumumab). The trial is closed and this is the final analysis. This trial is registered withClinicalTrials.gov, numberNCT00500760 . Findings: Between Oct 26, 2007, and March 26, 2009, 153 patients were enrolled and 150 received treatment (63 in the chemoradiotherapy group and 87 in the panitumumab plus chemoradiotherapy group). Local-regional control at 2 years was 68% (95% CI 54–78) in the chemoradiotherapy group and 61% (50–71) in the panitumumab plus chemoradiotherapy group. The most frequent grade 3–4 adverse events were dysphagia (17 [27%] of 63 patients in the chemoradiotherapy group vs 35 [40%] of 87 in the panitumumab plus chemoradiotherapy group), mucosal inflammation (15 [24%] vs 48 [55%]), and radiation skin injury (eight [13%] vs 27 [31%]). Serious adverse events were reported in 20 (32%) of 63 patients in the chemoradiotherapy group and in 37 (43%) of 87 patients in the panitumumab plus chemoradiotherapy group. Interpretation: In patients with locally advanced squamous-cell carcinoma of the head and neck, the addition of panitumumab to standard fractionation radiotherapy and cisplatin did not confer any benefit, and the role of EGFR inhibition in these patients needs to be reassessed. Funding: Amgen.